Comparison of microvessel densities in rat prostate tissues treated with finasteride, bicalutamide and surgical castration: A preliminary study - (:unkn) unknown (WILEY, 2005)
Background: A group of anti-androgens with different mechanisms of action and adverse effects have been investigated in patients with gross hematuria related to benign prostate hyperplasia; however, there is not yet any consensus about the standard management of these patients. The present study aims to identify if any one type of the hormonal intervention is superior in terms of the suppression of microvessel formation in the prostate. Materials and methods: A total of 28 mature, healthy male Sprague-Dawley rats (300 +/- 50 g) were used in this study. The rats were randomly assigned to one of four groups (n = 7 per group). The effects of three different hormonal therapies on angiogenesis and microvascularity in rat ventral prostate were compared. Groups 1 and 2 were treated for 28 days with finasteride and bicalutamide, respectively, and rats from Group 3 underwent surgical castration. Following treatment, all rats included in the study underwent dissection of the ventral prostate and immunohistochemical analysis of microvessel density by factor VIII-related antigen. Results: The mean number of microvessels in the finasteride and bicalutamide groups was 24.5 (+/-8.44 SE) and 27 (+/-9.89 SE) respectively. In contrast, the castration and control groups had microvessel numbers of 12.9 (+/-5.35 SE) and 40.3 (+/-5.03 SE) respectively. Differences were statistically significant between all three treatment groups and the controls (P < 0.005); the number of microvessels in rat prostate tissues of the control group was significantly higher than the treatment groups. Mean microvessel densities in the bicalutamide and finasteride groups were significantly higher than microvessel densities in the castration group (P < 0.005). There was no statistically significant difference between mean microvessel number in rat prostate tissue treated with finasteride or bicalutamide (P > 0.05). Conclusions: Even though finasteride was not as effective as castration in reducing microvessel number, its effect was equal to that of bicalutamide in terms of suppressing the angiogenesis in prostatic tissue. Based on the findings of the present study, finasteride might offer a viable option in the management of macroscopic hematuria by inhibition of microvessel formation within the prostatic tissue. Further clinical studies are warranted.
Keywords: angiogenesis; hormonal therapy; microvessel density; prostate; VENTRAL PROSTATE; BLOOD-FLOW